2006
DOI: 10.1158/1055-9965.epi-05-0334
|View full text |Cite
|
Sign up to set email alerts
|

Mesothelin Variant 1 Is Released from Tumor Cells as a Diagnostic Marker

Abstract: The mesothelin family comprises (at least) three variants and includes the precursor for megakaryocyte potentiating factor (MPF). Assaying soluble mesothelin-related protein (SMRP) molecules in serum and other body fluids from patients with certain cancers can provide diagnostically useful information. We have constructed fusion proteins of mesothelin variants 1, 2, and 3, made monoclonal antibodies, and investigated the binding specificity of these and three previously generated monoclonal antibodies to each … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
82
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(84 citation statements)
references
References 27 publications
2
82
0
Order By: Relevance
“…Supporting the first hypothesis, two variants of mesothelin with different N-terminal structures have been described but they represent less than 5% of mesothelin transcripts, and some authors hypothesised that they could be the result of a sequencing error or the cloning of an incompletely processed mRNA [40]. On the other side, it has been demonstrated that mesothelin is cleaved from the membrane but the mechanism (and the precise enzymes involved) is unknown [41][42][43]. There is no common agreement on how this molecule should be named: currently SMRP, soluble mesothelin or N-ERC/mesothelin are used in the literature and referred to the same molecule.…”
Section: Mesothelinmentioning
confidence: 99%
“…Supporting the first hypothesis, two variants of mesothelin with different N-terminal structures have been described but they represent less than 5% of mesothelin transcripts, and some authors hypothesised that they could be the result of a sequencing error or the cloning of an incompletely processed mRNA [40]. On the other side, it has been demonstrated that mesothelin is cleaved from the membrane but the mechanism (and the precise enzymes involved) is unknown [41][42][43]. There is no common agreement on how this molecule should be named: currently SMRP, soluble mesothelin or N-ERC/mesothelin are used in the literature and referred to the same molecule.…”
Section: Mesothelinmentioning
confidence: 99%
“…To the Editors: We read with great interest the article by Hellstrom et al (1) about characterization of soluble mesothelin proteins (SMP) in cancer patients. The authors found that the SMP in ascites from a patient with ovarian carcinoma contained the sequence of extracellular domain of a membrane-bound mesothelin (2, 3) rather than a soluble form speculated previously by Scholler et al (4).…”
Section: Mesothelin Is Shed From Tumor Cellsmentioning
confidence: 99%
“…42,43 ). There are three variants of these proteins, with variant 1 being most common [44][45][46] . These result from proteolytic cleavage of a part of a mesothelin molecule, probably by the action of a phospholipase or protease or by gene mutation 47,48 .…”
Section: Introductionmentioning
confidence: 99%